A study on impulsive buying behaviour among consumers in Kota Bharu / Nor Laili Nawi - Nawi, Nor Laili (2011)
This research is conducted to study the impulsive buying behavior in Kota Bharu, Kelantan. The objectives of this research are to know the relationships of individual’s mood, discount price and window display with impulsive buying behavior. This study also aims to find the major factor that associate with impulsive buying behavior among consumers. In collecting data, primary data is used. Questionnaires had been distributed in Kota Bharu area in order to get feedback from consumers. The result shows that there is an association or significant relationship between individual mood, discount price and window display with impulsive buying behavior among consumers